The postprandial dynamics of gastroduodenal zone hormones in patients with metabolic obesity associated or not associated with type 2 diabetes - Elena Vital'evna Kirienkova; Mariia Aleksandrovna Vasilenko; Pavel Anatol'evich Zatolokin; Nataliya Ivanovna Mironyuk; Dar'ya Aleksandrovna Skuratovskaia; Larisa Sergeevna Litvinova (Сахарный диабет)
Background. The main aims of the conservative treatment of metabolic obesity (MО) are weight loss and the prevention of type 2 diabetes. Incretin-based drugs are considered to be effective and safe and stimulate insulin secretion via the β-cells of the pancreas, and are widely used to restore impaired glucose tolerance. Bariatric surgery not only significantly reduces BMI but also normalises carbohydrate metabolism in patients with MО over a short period after the operation by increasing the secretion of endogenous incretins.Aim. To investigate hormone secretion in the gastroduodenal zone in patients with MО after Roux-en-Y gastric bypass before and after a test meal.Material and methods. We studied the plasma levels of insulin, C-peptide, glucagon, ghrelin and incretins (GIP and GLP-1) using flow fluorometry in 28 patients with MO (12 males and 16 females aged 29–63 years). Patients were divided into two groups: those who did not undergo gastric bypass surgeries and those after treatment (18 months).Results. We found a postprandial increase in the plasma GIP levels with respect to the baseline values in all subject groups, regardless of whether or not they had type 2 diabetes. A analysis of the levels of postprandial GLP-1 secretion revealed the existence of multidirectional dynamics of this indicator regardless of the presence of type 2 diabetes: an increase, decrease, or no difference in GLP-1 secretion was found compared to the measurements on an empty stomach.Conclusions. The postprandial GIP levels increased compared with baseline levels in all groups. The dynamics of the changes in the postprandial GLP-1 levels were multidirectional in patients with MО regardless of the presence of impaired glucose tolerance after Roux-en-Y gastric bypass. A positive correlation was observed between the plasma ghrelin levels and glucagon in all groups.